Pottery of Pikutkowo Type in the Funnel Beaker Culture: Characteristics, Dispersion and Context - Kośko, Aleksander; Szmyt, Marzena (Baltic-Pontic Studies, 2020)
The article discusses the current state of knowledge concerning the set of specific pottery characteristics of the Funnel Beaker culture that constitutes the so-called Pikutkowo stylistics. It is especially strongly represented in Kujawy, where the changes in the Pikutkowo set of characteristics define Phases IIIB and IIIB-C dated to 3700-3200 BC. Already in 3700/3650-3500 BC, Pikutkowo pottery appears not only on the Polish Lowland (including Wielkopolska and central Poland as well as the Chełmno Land and Gostynin Lake District), but also on the old Uplands in the upper Vistula basin. The latest data indicate that at the same time Pikutkowo characteristics are also present in Funnel Beaker assemblages from the Subcarpathian foothills and upper Dniester area. It is argued that this wide distribution delimits the Pikutkowo stylistics space, which was a zone of active circulation of cultural patterns within the Funnel Beaker culture. The culture-forming potential of this zone is best seen in the increased transfer of one of the key technological innovations of the Eneolithic, i.e. copper (including arsenic copper) use and processing.